The Youngest Palestinian Case of Multisystem Inflammatory Syndrome in children (MIS-C) - Mazen Abunejma, Fawzy; Muwaffaq Janem, Abdelrhman; Mohammad Awaysa, Asala; Nadi Kawazbeh, Waleed; Mohammed Hasan Awad, Rasha; saleh ilian khalil, Lamees; W. M. Jobran, Afnan (AL-Kindy College Medical Journal, 2022)
The multisystem inflammatory syndrome in children (MIS-C) considers a post-infectious immunological response to coronavirus illness (COVID-19) that was originally identified in the United Kingdom and later identified in other countries. A previously healthy 3-month-old boy was admitted to hospital context with -5-day history of fever, gastrointestinal symptoms [diarrhea, vomiting of normal gastric contents], hypoactivity, and poor oral intake, but so far no history of covid-19 active disease. The infant was dehydrated, with macular non-blanching skin rash everywhere over his body and widespread non-pitting edema. With supportive measures, methylprednisolone and IV immunoglobulin, the child improved, with his fever, skin rash, and laboratory tests returning to normal. On the seventh day of hospitalization, he was discharged. This is identified as the youngest reported case of MIS-C since the beginning of the COVID-19 pandemic